Therapeutic and Tectonic Penetrating Keratoplasty- All in One - Ng, WL.; Umi Kalthum MN.,; Jemaima CH.,; Then, KY. (Department of Surgery, UKM Medical Centre, 2015)
A middle-aged gentleman with history of left penetrating keratoplatsy presented with left eye perforated corneal graft secondary to infective keratitis. The affected eye was blind from absolute steroid-induced glaucoma. In view of expected poor graft survival in a blind eye, globe removal was offered. However, the patient refused the treatment and request for another corneal graft. This case highlights both the possibility of good outcome of cornea graft in such a case, and also illustrates that patient’s autonomy to refuse treatment option outweighs beneficence.